Simplified exponential approximation for thermodynamics of a hard-core repulsive Yukawa fluid - Hlushak, S.; Trokhymchuk, A. (Condensed Matter Physics, 2012)
Exponential approximation based on the first order mean spherical approximation (FMSA) is applied to the study of the structure and thermodynamics of hard-core repulsive Yukawa fluids. The proposed theory utilizes an exponential enhancement of the analytical solution of the FMSA due to Tang and Lu [J. Chem. Phys., 1993, 99, 9828] for the radial distribution function. From comparison with computer simulation data we have shown that at low density and low temperature conditions, where original FMSA theory fails, the FMSA-based exponential theory predicts a significant improvement. Експонентне наближення на основi середньо-сферичного наближення першого порядку (FMSA) застосовується до вивчення структури та термодинамiки твердосферного плину з юкавiвським вiдштовхуванням. Запропонована теорiя користується фактом, що iснує аналiтичний розв’язок FMSA, а звичайне експонентне наближення суттєво його покращує. Шляхом порiвняння з комп’ютерним експериментом показано, що в областi малих густин та низьких температур, там де теорiя середнього поля не працює, експонентне наближення приводить до суттєвого вдосконалення теоретичних передбачень.